Expanding the Spectrum of Attitudes Toward the Death Penalty: How Nondichotomous Response Options Affect Our Understandings of Death Penalty Attitudes. (June 2014) - Worthen, Meredith G. F.; Rodgers, Forrest R.; Sharp, Susan F.
Overall, studies show that the majority of Americans support the use of the death penalty for murderers; however, few studies have investigated response patterns to death penalty survey questions that offer more than yes/no response options. Without a realistic understanding of Americans' attitudes, the existence of this controversial legislation may hinge on inaccurate depictions of public opinion. The current study utilizes a college sample of students from a southern university ( N = 775, average age 22) to investigate how nondichotomous response options affect our understandings of death penalty attitudes. Using independent variables that are commonly found in quantitative studies about death penalty attitudes (i.e., religiosity, biblical literalism, political attitudes, race, gender, age, southern region) as well as independent variables less commonly seen in death penalty studies (i.e., feminist identity, and student-specific variables: grade point average, freshman status, high school size, and sociology major/minor), ordinary least squares and logistic regression results indicate that examining death penalty support with nondichotomous response options reveals more nuanced results when compared to examinations of death penalty that use dichotomous response options. Policy implications are discussed.